Accelerated Experimental Investigation on Long-term Performance Degradation of Heat Exchangers in Air Conditioners - Ju Peiling; Zhuang Dawei; Zhan Feilong; Ding Guoliang; Tang Jiajun (Zhileng xuebao)
To investigate the effect of deposited dust particles on the long-term performance degradation of outdoor air-conditioner units, acceleration experiments on dust deposition were carried out in the present study. An acceleration-experiment method for short-term dust deposition with high dust concentration was proposed to simulate the actual long-term dust deposition with low dust concentration, and an experimental rig was established to perform the accelerating-dust test. Acceleration experiments for 2–10 h were carried out on three types of heat-exchanger samples with different fin structures and tube row numbers, and the test results were used to predict the long-term performance degradation of outdoor heat exchangers operated for one to five years. The results show that after five years of operation, the air-side pressure drops of a one-tube wavy fin-and-tube heat exchanger, a two-tube wavy fin-and-tube heat exchanger, and a two-tube plate fin-and-tube heat exchanger were increased by 21.8%, 29.5%, and 25.0%, respectively. Meanwhile, the air-side heat-transfer capacity was reduced by 11.2%, 19.3%, and 18.0%, respectively.